Beta1-receptor blockade attenuates atherosclerosis progression following traumatic brain injury in apolipoprotein E deficient mice. - Jintao Wang; Jessica Venugopal; Paul Silaghi; Enming J Su; Chiao Guo; Daniel A Lawrence; Daniel T Eitzman (PLoS ONE)
Traumatic brain injury (TBI) is associated with cardiovascular mortality in humans. Enhanced sympathetic activity following TBI may contribute to accelerated atherosclerosis. The effect of beta1-adrenergic receptor blockade on atherosclerosis progression induced by TBI was studied in apolipoprotein E deficient mice. Mice were treated with metoprolol or vehicle following TBI or sham operation. Mice treated with metoprolol experienced a reduced heart rate with no difference in blood pressure. Six weeks following TBI, mice were sacrificed for analysis of atherosclerosis. Total surface area and lesion thickness, analyzed at the level of the aortic valve, was found to be increased in mice receiving TBI with vehicle treatment but this effect was ameliorated in TBI mice receiving metoprolol. No effect of metoprolol on atherosclerosis was observed in mice receiving only sham operation. In conclusion, accelerated atherosclerosis following TBI is reduced with beta-adrenergic receptor antagonism. Beta blockers may be useful to reduce vascular risk associated with TBI.